Composite material as well as preparation method and application thereof

By using composite materials of stereocomposites and inorganic minerals in bone tissue repair materials, the problems of insufficient strength and poor adjustability of existing PLA-PEG-PLA materials are solved, and higher stability and strength are achieved, which are suitable for a variety of bone tissue repair needs.

CN119868644APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311387778.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing triblock polymer PLA-PEG-PLA has weak interactions, resulting in insufficient material strength, poor adjustability, and poor processability, making it difficult to meet the needs of bone tissue repair in different parts of the human body.

Method used

Composite materials using stereocomposites and inorganic minerals, including levopolylactic acid-polyethylene glycol-levopolylactic acid block copolymer and dextropolylactic acid-polyethylene glycol-dextropolylactic acid block copolymer, form composite materials with higher strength and controllable properties through specific molar ratios and addition of inorganic minerals.

Benefits of technology

It improves the stability and strength of composite materials, improves processability, and realizes controllable adjustment of bone tissue repair performance, which is suitable for bone tissue repair in different parts of the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004512307010000151
    Figure BDA0004512307010000151
  • Figure BDA0004512307010000161
    Figure BDA0004512307010000161
Patent Text Reader

Abstract

The invention relates to the technical field of biological materials, and discloses a composite material as well as a preparation method and application thereof. The composite material comprises a three-dimensional compound and an inorganic mineral substance, the three-dimensional compound comprises a poly (L-lactic acid)-polyethylene glycol-poly (L-lactic acid) block copolymer and a poly (D-lactic acid)-polyethylene glycol-poly (D-lactic acid) block copolymer, the molar ratio of the poly (L-lactic acid)-polyethylene glycol-poly (L-lactic acid) block copolymer to the poly (D-lactic acid)-polyethylene glycol-poly (D-lactic acid) block copolymer is 1: (0.1-10). The poly-L-lactic acid-polyethylene glycol-poly-L-lactic acid block copolymer and the poly-D-lactic acid-polyethylene glycol-poly-D-lactic acid block copolymer have a specific molar ratio, so that the composite material has better stability and higher strength, and the processability is also improved; the performance of the composite material can be controlled, so that the requirements of bone tissue repair of different parts of a human body are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomaterials, and in particular to a composite material and a preparation method and application thereof. Background Art

[0002] At present, bone loss and fractures have become a hot topic. Relevant data show that there are more than 2.2 million bone grafting surgeries worldwide each year, which has greatly stimulated the research on bone regeneration and repair. At present, the number of osteoporosis patients in my country is close to 70 million, plus more than 80 million severe arthritis patients in my country, about 750,000 limb disability patients, and about 3 million new bone injury patients each year. Therefore, artificial bone materials for bone tissue repair have great development prospects. At present, clinical treatment usually uses autologous bone tissue transplantation for repair, but due to the limited amount of available bone tissue, this method cannot be applied to the repair of relatively large bone defects, and the cutting of bone tissue will bring additional pain to patients. Using biodegradable scaffolds to induce bone defect repair can avoid similar problems. The scaffold needs to have suitable mechanical properties, excellent processability, and through-holes to ensure the free migration of cells and the effective transportation of oxygen and nutrients. At the same time, it needs to meet the conditions of degradation time matching bone tissue regeneration and repair, convenient operation, and low cost. Commonly used inorganic materials such as hydroxyapatite, β-calcium phosphate, bioglass, etc., as well as natural polymers such as collagen and chitosan, cannot meet these performance requirements at the same time. Synthetic in vivo degradable polymers such as polylactic acid (PLA), polyglycolic acid (PGA), polycaprolactone (PCL), etc. have excellent mechanical and processing properties, adjustable degradation time, and low large-scale production costs. They are a class of very potential bone tissue repair materials. However, since the hydrophobicity of polyester polymers is not conducive to cell adhesion and growth, their effect on repairing bone damage is not ideal. In order to solve this problem, Professor Jie Song of the University of Massachusetts Medical School introduced hydrophilic polyethylene glycol (PEG) segments into PLA to make modified triblock polymers PLA-PEG-PLA. The introduction of hydrophilic segments can effectively help cell adhesion, thereby improving the tissue regeneration and repair function of the material. However, the interaction between the triblock polymer chains is weak, resulting in insufficient polymer strength and poor adjustability, which is difficult to meet the needs of bone tissue repair in different parts of the human body. At the same time, weak interactions also lead to low polymer melt strength and poor processability, limiting the application of the material. Summary of the invention

[0003] The purpose of the present invention is to overcome the problems in the prior art that the interaction between the triblock polymers PLA-PEG-PLA is weak, resulting in insufficient material strength and poor adjustability, poor processability and difficulty in meeting the needs of bone tissue repair in different parts of the human body, and to provide a composite material and a preparation method and application thereof.

[0004] In order to achieve the above-mentioned object, the present invention provides a composite material in a first aspect, characterized in that the composite material comprises a stereocomplex and an inorganic mineral;

[0005] The stereocomplex comprises L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer, and the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer to the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer is 1:0.1-10.

[0006] A second aspect of the present invention provides a method for preparing a composite material, characterized in that the method comprises the following steps:

[0007] S1. In the presence of a first catalyst, polyethylene glycol I and L-lactide are uniformly mixed and then subjected to a first polymerization reaction to obtain a L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer;

[0008] S2. In the presence of a second catalyst, polyethylene glycol II and D-lactide are uniformly mixed and then subjected to a second polymerization reaction to obtain a dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer;

[0009] S3, mixing the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer, heating to a molten state and stirring, and cooling to form a stereocomplex;

[0010] S4, mixing the three-dimensional complex with an inorganic mineral, and processing and molding to obtain a composite material;

[0011] Wherein, the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer after mixing is 1:0.1-10;

[0012] The molar ratio of the polyethylene glycol I to the L-lactide is 1:120-10000;

[0013] The molar ratio of the polyethylene glycol II to the D-lactide is 1:120-10000.

[0014] The third aspect of the present invention provides a composite material prepared by the method described in the second aspect.

[0015] The fourth aspect of the present invention provides a use of the composite material described in the first aspect or the third aspect in bone tissue repair.

[0016] Through the above technical solution, the composite material provided by the present invention and its preparation method and application obtain the following beneficial effects:

[0017] (1) Based on the chirality of the molecule, the present invention mixes block copolymers containing polylactic acid enantiomers without changing the molecular composition of the polymer to form a stereocomplex, so that the composite material has better stability and higher strength, and the processability is also improved;

[0018] (2) The L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer described in the present invention have a specific molar ratio, which can achieve controllable performance of the composite material to meet the needs of bone tissue repair in different parts of the human body. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] A first aspect of the present invention provides a composite material, characterized in that the composite material comprises a stereocomplex and an inorganic mineral;

[0021] The stereocomplex comprises L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer, and the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer to the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer is 1:0.1-10.

[0022] In the present invention, the structure of the stereocomplex is: hydrophilic PEG in the middle and hydrophobic degradable polylactic acid (PLA) at both ends, and the PLA contains left-handed polylactic acid (PLLA) and right-handed polylactic acid (PDLA) which are enantiomers of each other.

[0023] In the present invention, the inventors have found that PLLA and PDLA are enantiomers of each other, and there is a stronger interaction between the enantiomers, which is called a stereocomplex. Due to the existence of the interaction, the stereocomplex has better stability, and the prepared material also has higher strength. At the same time, due to the existence of the interaction, the melt strength of the material is also enhanced, so that it has better processing properties. By mixing left-handed polylactic acid-polyethylene glycol-left-handed polylactic acid block copolymer (PLLA-PEG-PLLA) and right-handed polylactic acid-polyethylene glycol-right-handed polylactic acid block copolymer (PDLA-PEG-PDLA) in a specific ratio, and then mixing with inorganic minerals, processing and molding to obtain a composite material. In addition, by adjusting the ratio of enantiomers, the strength of the composite material can be controlled and adjusted, thereby further expanding the application range of the material.

[0024] In the present invention, the composite material contains a specific ratio of L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer, so that the composite material has better stability and higher strength, while improving its processability, and can be well used for bone tissue repair in different parts of the human body.

[0025] In the present invention, it should be noted that the "mole" in the molar ratio refers to the molar amount of the entire L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and the entire D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer.

[0026] According to the present invention, the composite material comprises 30 wt% to 95 wt% of the stereocomplex and 5 wt% to 70 wt% of the inorganic mineral.

[0027] In the present invention, the contents of the stereocomplex and the inorganic mineral satisfy the above ranges, and can have an excellent bone tissue repairing effect.

[0028] Furthermore, the composite material comprises 50 wt% to 90 wt% of the stereocomplex and 10 wt% to 50 wt% of the inorganic mineral.

[0029] According to the present invention, the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer to the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer is 1:0.5-2.

[0030] According to the present invention, the inorganic mineral is selected from at least one of calcium phosphate, hydroxyapatite, bioglass and calcium carbonate.

[0031] According to the present invention, based on the total amount of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer, the content of the polyethylene glycol segment is 7wt%-67wt%, and the content of the L-polylactic acid segment is 33wt%-93wt%.

[0032] In the present invention, the "L-polylactic acid segment" refers to the L-polylactic acid segments at both ends of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer.

[0033] According to the present invention, based on the total amount of the dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer, the content of the polyethylene glycol segment is 7wt%-67wt%, and the content of the dextrorotatory polylactic acid segment is 33wt%-93wt%.

[0034] In the present invention, the "dextral polylactic acid segment" refers to the dextrorotatory polylactic acid segments at both ends of the dextrorotatory polylactic acid-polyethylene glycol-dextral polylactic acid block copolymer.

[0035] According to the present invention, the number average molecular weight of the poly(L-lactic acid)-polyethylene glycol-poly(L-lactic acid) block copolymer is 30,000-300,000 g / mol.

[0036] According to the present invention, the number average molecular weight of the dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer is 30,000-300,000 g / mol.

[0037] In the present invention, the number average molecular weight of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer meets the above range and can match the mechanical properties of bone tissue.

[0038] Furthermore, the number average molecular weight of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer is 60,000-150,000 g / mol.

[0039] Furthermore, the number average molecular weight of the dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer is 60,000-150,000 g / mol.

[0040] According to the present invention, the melt index of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer at 190° C. and a load of 2.16 kg is 1-50 g / 10 min, preferably 5-30 g / 10 min.

[0041] According to the present invention, the melt index of the dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer at 190° C. and a load of 2.16 kg is 1-50 g / 10 min, preferably 5-30 g / 10 min.

[0042] According to the present invention, the average pore size of the composite material is 200-800 μm, and the porosity is ≥40%.

[0043] A second aspect of the present invention provides a method for preparing a composite material, characterized in that the method comprises the following steps:

[0044] S1. In the presence of a first catalyst, polyethylene glycol I and L-lactide are uniformly mixed and then subjected to a first polymerization reaction to obtain a L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer;

[0045] S2. In the presence of a second catalyst, polyethylene glycol II and D-lactide are uniformly mixed and then subjected to a second polymerization reaction to obtain a dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer;

[0046] S3, mixing the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer, heating to a molten state and stirring, and cooling to form a stereocomplex;

[0047] S4, mixing the three-dimensional complex with an inorganic mineral, and processing and molding to obtain a composite material;

[0048] Wherein, the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer to the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer is 1:0.1-10;

[0049] The molar ratio of the polyethylene glycol I to the L-lactide is 1:120-10000;

[0050] The molar ratio of the polyethylene glycol II to the D-lactide is 1:120-10000.

[0051] In the present invention, the polyethylene glycol I and the polyethylene glycol II need to be freed of water and impurities before use, and the pretreatment conditions can adopt conventional treatment methods in the art, such as heating at 100-150° C. under vacuum for 1-3 h.

[0052] According to the present invention, the first catalyst and the second catalyst are each independently selected from at least one of stannous isooctanoate, stannous octoate, tributylaluminum and diethylzinc.

[0053] According to a preferred embodiment of the present invention, the first catalyst and the second catalyst are configured into a toluene solution before use so as to be better added into the system.

[0054] According to the present invention, the amount of the first catalyst used is 0.1 wt%-1 wt% of the polyethylene glycol I.

[0055] According to the present invention, the amount of the second catalyst is 0.1 wt%-1 wt% of the polyethylene glycol II.

[0056] In the present invention, the usage of the first catalyst and the second catalyst meets the above range and can reach the metal content standard of medical-grade catalysts.

[0057] Furthermore, the first catalyst is used in an amount of 0.2 wt%-0.6 wt% of polyethylene glycol I, and the second catalyst is used in an amount of 0.2 wt%-0.6 wt% of polyethylene glycol II.

[0058] According to the present invention, the first polymerization reaction and the second polymerization reaction independently include: a reaction temperature of 100-200° C., preferably 120-160° C.; and a reaction time of 3-6 hours, preferably 4-5 hours.

[0059] According to the present invention, the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer to the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer is 1:0.5-2.

[0060] According to the present invention, the number average molecular weight of the polyethylene glycol I and the polyethylene glycol II is independently 2000-200000 g / mol, preferably 10000-50000 g / mol.

[0061] According to a particularly preferred embodiment of the present invention, the molar ratio of the polyethylene glycol I to L-lactide is 1:200-2000, and the molar ratio of the polyethylene glycol II to D-lactide is 1:200-2000.

[0062] In the present invention, when the molar ratio of the polyethylene glycol I to L-lactide and the molar ratio of the polyethylene glycol II to D-lactide meet the above ranges, it can be ensured that the number average molecular weight of the formed polymer meets the requirements, and thus has satisfactory melt strength and modulus.

[0063] According to the present invention, in step S3, the stirring conditions include: stirring time of 1-10 min, preferably 3-6 min; stirring temperature of 150-250°C, preferably 170-210°C.

[0064] According to the present invention, in step S4, the mass of the inorganic mineral material is 5wt%-70wt% based on the weight of the composite material.

[0065] In the present invention, the mass of the inorganic minerals satisfies the above range and can have an excellent bone tissue repairing effect.

[0066] Furthermore, based on the weight of the composite material, the mass of the inorganic mineral material is 10wt%-50wt%.

[0067] According to the present invention, the inorganic mineral is selected from at least one of calcium phosphate, hydroxyapatite, bioglass and calcium carbonate.

[0068] According to the present invention, the processing and forming method is electrospinning and / or 3D printing.

[0069] In the present invention, the forming mode of electrostatic spinning is exemplarily described. Wherein, the method of electrostatic spinning is: the mixture obtained by mixing the stereocomplex with the inorganic mineral is added to a syringe (for example, the needle model can be 22G), an aluminum disk is placed 10-20cm below the needle, and a 10-25kV high voltage is applied between the aluminum disk and the needle. The mixture is extruded at a rate of 0.5-1.5mL / h. To ensure that the support is uniform, the aluminum disk is rotated at a certain angle (45-90°) every 10-15min during the process. The obtained stereocomplex support is dried in a vacuum oven for standby use.

[0070] In the present invention, the inner diameter of the needle, the distance between the needle and the aluminum disk, the pressure between the aluminum disk and the needle, the extrusion rate of the mixture, and the rotation angle and method of the aluminum disk are all conventional methods. The above data are only illustrative of the operation and are not intended to limit it.

[0071] Further, the 3D printing method is illustratively as follows: the mixture obtained by mixing the three-dimensional composite material with the inorganic mineral is poured into a Teflon mold, placed in a fume hood for 12 hours, and then completely dried in an oven and cut into small pieces. The mixture cut into small pieces is made into filaments with a diameter of 1.75 mm using a capillary rheometer, and the filaments are printed into a composite material of a desired size using a 3D printer.

[0072] In the present invention, the placement time after the mixture is poured into the Teflon mold, the size of the small pieces, the size of the filaments, and the size of the composite material are only exemplary for the operation and are not intended to limit the same.

[0073] In the present invention, before mixing the stereocomplex with the inorganic mineral, the inorganic mineral is preferably dispersed in an organic solvent and ultrasonically mixed, and then the stereocomplex is added and stirred to obtain a mixture. The organic solvent is chloroform or a mixed solvent of chloroform / dimethylformamide, wherein the mass ratio of chloroform to dimethylformamide is 1-4:1.

[0074] In the present invention, the ultrasonic conditions are not particularly limited, as long as the inorganic minerals can be evenly dispersed in the organic solvent. Similarly, the stirring conditions after adding the stereocomplex are not particularly limited, for example, stirring can be performed at room temperature for at least 12 hours.

[0075] According to a preferred embodiment of the present invention, the method comprises the following steps:

[0076] S1. Heating PEG at 100-150° C. under vacuum conditions for 1-3 h to remove water and impurities, and in the presence of a first catalyst, mixing polyethylene glycol I and L-lactide at a molar ratio of 1:200-2000, and then performing a first polymerization reaction at 120-160° C. for 4-5 h to obtain a L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer having a number average molecular weight of 60,000-150,000 g / mol;

[0077] S2. In the presence of a second catalyst, polyethylene glycol II and D-lactide are uniformly mixed and then subjected to a second polymerization reaction at 120-160° C. for 4-5 hours to obtain a dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer;

[0078] S3, mixing the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer, heating to a molten state at 180-200° C., stirring for 3-6 minutes, and cooling to form a stereocomplex;

[0079] S4, dissolving the inorganic mineral in chloroform, adding the stereocomplex after ultrasonic treatment for 20-40 minutes, stirring at room temperature, and processing to obtain a composite material;

[0080] Wherein, the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer after mixing is 1:0.5-2;

[0081] The molar ratio of the polyethylene glycol I to the L-lactide is 1:200-10000;

[0082] The molar ratio of the polyethylene glycol II to the D-lactide is 1:200-10000.

[0083] The third aspect of the present invention provides a composite material prepared by the method described in the second aspect.

[0084] In the present invention, the product has the appearance of a white or light yellow solid.

[0085] The fourth aspect of the present invention provides a use of the composite material described in the first aspect and / or the third aspect in bone tissue repair.

[0086] The present invention will be described in detail below by way of examples. In the following examples,

[0087] The modulus of the composites was measured by dynamic thermomechanical analysis;

[0088] Melt strength is measured by melt strength tester method;

[0089] The degradation time was measured by the following method: the prepared sample was placed in a cell culture medium and then placed on a shaker and observed every 7 days. When the sample was completely dissolved, the time taken was the degradation time;

[0090] PEG, purchased from Sigma-Aldrich;

[0091] Tributylaluminum, purchased from Sigma-Aldrich;

[0092] Stannous octoate, purchased from Sigma-Aldrich;

[0093] Stannous isooctanoate, purchased from Sigma-Aldrich;

[0094] L-lactide, purchased from Sigma-Aldrich;

[0095] D-lactide was purchased from Sigma-Aldrich.

[0096] Example 1

[0097] S1. Add 4 g PEG (number average molecular weight 20000 g / mol) to the reaction bottle I, heat at 100° C. under vacuum for 2 h to remove water and impurities, add 0.2 mL of stannous isooctanoate toluene solution (100 mg / mL) to the reaction bottle (the effective mass of the catalyst is 20 mg), and heat at 100° C. under vacuum for 15 min to remove toluene and impurities; add 15 g L-lactide to the reaction bottle, and carry out a first polymerization reaction at 130° C. for 4 h to obtain PLLA-PEG-PLLA with a number average molecular weight of 100000 g / mol;

[0098] S2, add 4g PEG (number average molecular weight 20000g / mol) to the reaction bottle II, heat at 100°C and vacuum for 2h to remove water and impurities, add 0.2mL of stannous isooctanoate toluene solution (100mg / mL) to the reaction bottle (the effective mass of the catalyst is 20mg), and heat at 100°C and vacuum for 15min to remove toluene and impurities; add 15g D-lactide to the reaction bottle, and carry out the first polymerization reaction at 130°C for 4h to obtain PDLA-PEG-PDLA with a number average molecular weight of 100000g / mol;

[0099] S3, mixing PLLA-PEG-PLLA and PDLA-PEG-PDLA, heating at 190°C until they are molten, stirring for 20 minutes, and cooling naturally to form a stereocomplex;

[0100] S4, add 0.28g hydroxyapatite to 10mL chloroform / dimethylformamide mixed solvent (volume ratio 4:1), add 2.5g stereocomplex after ultrasonication for 40min, stir at room temperature for 12h, add the mixture into a syringe (needle is 22G), place an aluminum plate 15cm below, and apply 12kV high voltage between the aluminum plate and the needle. Extrude the mixture at a speed of 1mL / h. To ensure uniformity of the scaffold, rotate the aluminum plate 90° every 15min during the process. Obtain composite material A1.

[0101] Among them, the molar ratio of PLLA-PEG-PLLA and PDLA-PEG-PDLA, the amount of the first catalyst, the amount of the second catalyst, the molar ratio of PEG to L-lactide, the molar ratio of PEG to D-lactide, and the mass ratio of the stereocomplex to the inorganic mineral are shown in Table 1.

[0102] The contents of the stereocomplex and the inorganic minerals, the contents of the PLLA segments and the PEG segments in PLLA-PEG-PLLA, the contents of the PDLA segments and the PEG segments in PDLA-PEG-PDLA, the melt indexes of PLLA-PEG-PLLA and PDLA-PEG-PDLA, and the average pore size of the composite materials are shown in Table 2 and Table 2 (Continued).

[0103] Example 2

[0104] S1. Add 4 g PEG (number average molecular weight 20000 g / mol) to the reaction bottle I, heat at 100° C. under vacuum for 2 h to remove water and impurities, add 0.2 mL of stannous isooctanoate toluene solution (100 mg / mL) to the reaction bottle (the effective mass of the catalyst is 20 mg), and heat at 100° C. under vacuum for 15 min to remove toluene and impurities; add 15 g L-lactide to the reaction bottle, and carry out a first polymerization reaction at 130° C. for 4 h to obtain PLLA-PEG-PLLA with a number average molecular weight of 100000 g / mol;

[0105] S2, add 4g PEG (number average molecular weight 20000g / mol) to the reaction bottle II, heat at 100°C and vacuum for 2h to remove water and impurities, add 0.2mL of stannous isooctanoate toluene solution (100mg / mL) to the reaction bottle (the effective mass of the catalyst is 20mg), and heat at 100°C and vacuum for 15min to remove toluene and impurities; add 15g D-lactide to the reaction bottle, and carry out the first polymerization reaction at 130°C for 4h to obtain PDLA-PEG-PDLA with a number average molecular weight of 100000g / mol;

[0106] S3, mixing PLLA-PEG-PLLA and PDLA-PEG-PDLA, heating at 190°C until they are molten, stirring for 20 minutes, and cooling naturally to form a stereocomplex;

[0107] S4, 1.12g hydroxyapatite was added to 40mL chloroform, and 10g stereocomplex was added after ultrasonic treatment for 20min. After stirring at room temperature for 12h, the mixture was poured into a Teflon mold, placed in a fume hood for 12h, and then completely dried in an oven and cut into small pieces. The stereocomplex was made into 1.75mm filaments using a capillary rheometer, and the filaments were printed into 15mm×15mm×15mm composite material A2 using a 3D printer.

[0108] Among them, the molar ratio of PLLA-PEG-PLLA and PDLA-PEG-PDLA, the amount of the first catalyst, the amount of the second catalyst, the molar ratio of PEG to L-lactide, the molar ratio of PEG to D-lactide, and the mass ratio of the stereocomplex to the inorganic mineral are shown in Table 1.

[0109] The contents of the stereocomplex and the inorganic minerals, the contents of the PLLA segments and the PEG segments in PLLA-PEG-PLLA, the contents of the PDLA segments and the PEG segments in PDLA-PEG-PDLA, the melt indexes of PLLA-PEG-PLLA and PDLA-PEG-PDLA, and the average pore size of the composite materials are shown in Table 2 and Table 2 (Continued).

[0110] Example 3

[0111] The method of Example 1 is followed, except that in step S4, the mass of PLLA-PEG-PLLA in 2.5 g of the stereocomplex is 2.27 g, and the mass of PDLA-PEG-PDLA is 0.23 g.

[0112] Among them, the molar ratio of PLLA-PEG-PLLA and PDLA-PEG-PDLA, the amount of the first catalyst, the amount of the second catalyst, the molar ratio of PEG to L-lactide, the molar ratio of PEG to D-lactide, and the mass ratio of the stereocomplex to the inorganic mineral are shown in Table 1.

[0113] The contents of the stereocomplex and the inorganic minerals, the contents of the PLLA segments and the PEG segments in PLLA-PEG-PLLA, the contents of the PDLA segments and the PEG segments in PDLA-PEG-PDLA, the melt indexes of PLLA-PEG-PLLA and PDLA-PEG-PDLA, and the average pore size of the composite materials are shown in Table 2 and Table 2 (Continued).

[0114] Example 4

[0115] The method of Example 1 is followed, except that the amount of the toluene solution of stannous isooctanoate (100 mg / mL) used in step S1 is 0.06 mL (the effective mass of the catalyst is 6 mg).

[0116] Among them, the molar ratio of PLLA-PEG-PLLA and PDLA-PEG-PDLA, the amount of the first catalyst, the amount of the second catalyst, the molar ratio of PEG to L-lactide, the molar ratio of PEG to D-lactide, and the mass ratio of the stereocomplex to the inorganic mineral are shown in Table 1.

[0117] The contents of the stereocomplex and the inorganic minerals, the contents of the PLLA segments and the PEG segments in PLLA-PEG-PLLA, the contents of the PDLA segments and the PEG segments in PDLA-PEG-PDLA, the melt indexes of PLLA-PEG-PLLA and PDLA-PEG-PDLA, and the average pore size of the composite materials are shown in Table 2 and Table 2 (Continued).

[0118] Example 5

[0119] The method of Example 1 was followed, except that the amount of hydroxyapatite used was 0.13 g.

[0120] Among them, the molar ratio of PLLA-PEG-PLLA and PDLA-PEG-PDLA, the amount of the first catalyst, the amount of the second catalyst, the molar ratio of PEG to L-lactide, the molar ratio of PEG to D-lactide, and the mass ratio of the stereocomplex to the inorganic mineral are shown in Table 1.

[0121] The contents of the stereocomplex and the inorganic minerals, the contents of the PLLA segments and the PEG segments in PLLA-PEG-PLLA, the contents of the PDLA segments and the PEG segments in PDLA-PEG-PDLA, the melt indexes of PLLA-PEG-PLLA and PDLA-PEG-PDLA, and the average pore size of the composite materials are shown in Table 2 and Table 2 (Continued).

[0122] Comparative Example 1

[0123] The method of Example 1 was followed, except that in step S4, the mass of PLLA-PEG-PLLA in 2.5 g of the stereocomplex was 0.19 g, and the mass of PDLA-PEG-PDLA was 2.31 g.

[0124] Among them, the molar ratio of PLLA-PEG-PLLA and PDLA-PEG-PDLA, the amount of the first catalyst, the amount of the second catalyst, the molar ratio of PEG to L-lactide, the molar ratio of PEG to D-lactide, and the mass ratio of the stereocomplex to the inorganic mineral are shown in Table 1.

[0125] The contents of the stereocomplex and the inorganic minerals, the contents of the PLLA segments and the PEG segments in PLLA-PEG-PLLA, the contents of the PDLA segments and the PEG segments in PDLA-PEG-PDLA, the melt indexes of PLLA-PEG-PLLA and PDLA-PEG-PDLA, and the average pore size of the composite materials are shown in Table 2 and Table 2 (Continued).

[0126] Comparative Example 2

[0127] The method of Example 1 is followed, except that step S2 is not performed, and PLLA-PEG-PLLA is directly heated at 190° C. to a molten state, stirred for 20 minutes, and cooled naturally to form a stereocomplex.

[0128] Among them, the molar ratio of PLLA-PEG-PLLA and PDLA-PEG-PDLA, the amount of the first catalyst, the amount of the second catalyst, the molar ratio of PEG to L-lactide, the molar ratio of PEG to D-lactide, and the mass ratio of the stereocomplex to the inorganic mineral are shown in Table 1.

[0129] The contents of the stereocomplex and the inorganic minerals, the contents of the PLLA segments and the PEG segments in PLLA-PEG-PLLA, the contents of the PDLA segments and the PEG segments in PDLA-PEG-PDLA, the melt indexes of PLLA-PEG-PLLA and PDLA-PEG-PDLA, and the average pore size of the composite materials are shown in Table 2 and Table 2 (Continued).

[0130] Comparative Example 3

[0131] The method of Example 1 is followed, except that in step S1, the amount of PEG used is 20 g, and in step S2, the amount of PEG used is 20 g.

[0132] Among them, the molar ratio of PLLA-PEG-PLLA and PDLA-PEG-PDLA, the amount of the first catalyst, the amount of the second catalyst, the molar ratio of PEG to L-lactide, the molar ratio of PEG to D-lactide, and the mass ratio of the stereocomplex to the inorganic mineral are shown in Table 1.

[0133] The contents of the stereocomplex and the inorganic minerals, the contents of the PLLA segments and the PEG segments in PLLA-PEG-PLLA, the contents of the PDLA segments and the PEG segments in PDLA-PEG-PDLA, the melt indexes of PLLA-PEG-PLLA and PDLA-PEG-PDLA, and the average pore size of the composite materials are shown in Table 2 and Table 2 (Continued).

[0134] Table 1

[0135]

[0136] a Refers to the molar ratio of PLLA-PEG-PLLA and PDLA-PEG-PDLA

[0137] b Refers to the amount of the first catalyst

[0138] c Refers to the amount of the second catalyst

[0139] d Refers to the amount of inorganic minerals relative to the composite material

[0140] Table 2

[0141]

[0142]

[0143] Table 2 (continued)

[0144] serial number Stereocomplex content / wt% Inorganic mineral content / wt% Average pore size / nm Porosity / % Example 1 89.9 10.1 600μm 66 Example 2 89.9 10.1 600μm 66 Example 3 89.9 10.1 600μm 66 Example 4 89.9 10.1 600μm 66 Example 5 95 5 600μm 66 Comparative Example 1 89.9 10.1 600μm 66 Comparative Example 2 89.9 10.1 600μm 66 Comparative Example 3 89.9 10.1 600μm 66

[0145] Test Case

[0146] The composite materials prepared in the examples and comparative examples were tested for modulus, melt strength and degradation time. The results are shown in Table 3.

[0147] Table 3

[0148] Compression modulus (kPa) Melt strength (mN) Degradation time (weeks) Example 1 360 30 18 Example 2 350 30 16 Example 3 120 12 15 Example 4 290 25 16 Example 5 330 26 18 Comparative Example 1 115 11 Almost no degradation Comparative Example 2 110 9 13 Comparative Example 3 80 5 8

[0149] From the above results, it can be seen that Examples 1-5 using the PLA-PEG-PLA stereocomplex of the present invention have higher compression modulus and melt strength and suitable degradation time. Among them, the compression modulus is not less than 120 kPa, and the melt strength is not less than 12 mN. And the degradation time is suitable, and the degradation is basically completed within 15-20 weeks.

[0150] However, in Comparative Example 1, the molar ratio of PLLA-PEG-PLLA to PDLA-PEG-PDLA is too high, resulting in decreased mechanical properties and almost no degradation in vivo. Comparative Example 2 does not contain PDLA-PEG-PDLA, and the molar ratio of polyethylene glycol to lactide in Comparative Example 3 is too low, both resulting in decreased strength of the composite material and being unable to be well applied in the field of bone tissue repair.

[0151] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite material, characterized in that: The composite material comprises a stereocomplex and an inorganic mineral; The stereocomplex comprises L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer, and the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer to the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer is 1:0.1-10.

2. The composite material according to claim 1, wherein The composite material comprises 30 wt% to 95 wt% of a stereocomplex and 5 wt% to 70 wt% of an inorganic mineral; Preferably, the composite material comprises 50 wt% to 90 wt% of the stereocomplex and 10 wt% to 50 wt% of the inorganic mineral; Preferably, the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer to the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer is 1:0.5-2; Preferably, the inorganic mineral is selected from at least one of calcium phosphate, hydroxyapatite, bioglass and calcium carbonate.

3. The composite material according to claim 1 or 2, wherein: Based on the total weight of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer, the content of the polyethylene glycol segment is 7wt%-67wt%, and the content of the L-polylactic acid segment is 33wt%-93wt%; Preferably, based on the total weight of the dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer, the content of the polyethylene glycol segment is 7wt%-67wt%, and the content of the dextrorotatory polylactic acid segment is 33wt%-93wt%.

4. The composite material according to any one of claims 1 to 3, wherein: The number average molecular weight of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer is 30000-300000 g / mol, preferably 60000-150000 g / mol; Preferably, the number average molecular weight of the dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer is 30000-300000 g / mol, preferably 60000-150000 g / mol; Preferably, the melt index of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer at 190° C. and a load of 2.16 kg is 1-50 g / 10 min, preferably 5-30 g / 10 min; Preferably, the melt index of the dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer at 190° C. and a load of 2.16 kg is 1-50 g / 10 min, preferably 5-30 g / 10 min.

5. The composite material according to any one of claims 1 to 4, wherein: The average pore size of the composite material is 200-800 μm, and the porosity is ≥40%.

6. A method for preparing a composite material, characterized in that: The method comprises the following steps: S1. In the presence of a first catalyst, polyethylene glycol I and L-lactide are uniformly mixed and then subjected to a first polymerization reaction to obtain a L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer; S2. In the presence of a second catalyst, polyethylene glycol II and D-lactide are uniformly mixed and then subjected to a second polymerization reaction to obtain a dextrorotatory polylactic acid-polyethylene glycol-dextrorotatory polylactic acid block copolymer; S3, mixing the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer and the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer, heating to a molten state and stirring, and cooling to form a stereocomplex; S4, mixing the three-dimensional complex with an inorganic mineral, and processing and molding to obtain a composite material; Wherein, the molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer to the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer is 1:0.1-10; The molar ratio of the polyethylene glycol I to the L-lactide is 1:120-10000; The molar ratio of the polyethylene glycol II to the D-lactide is 1:120-10000.

7. The method according to claim 6, wherein: The first catalyst and the second catalyst are each independently selected from at least one of stannous isooctanoate, stannous octoate, tributylaluminum and diethylzinc; Preferably, the first catalyst is used in an amount of 0.1wt%-1wt% of the polyethylene glycol I, preferably 0.2wt%-0.6wt%; Preferably, the second catalyst is used in an amount of 0.1wt%-1wt% of polyethylene glycol II, preferably 0.2wt%-0.6wt%; Preferably, the first polymerization reaction and the second polymerization reaction each independently include: a reaction temperature of 100-200° C., preferably 120-160° C.; and a reaction time of 3-6 h, preferably 4-5 h.

8. The method according to claim 6 or 7, wherein: The molar ratio of the L-polylactic acid-polyethylene glycol-L-polylactic acid block copolymer to the D-polylactic acid-polyethylene glycol-D-polylactic acid block copolymer is 1:0.5-2; The number average molecular weight of the polyethylene glycol I and the polyethylene glycol II is independently 2000-200000 g / mol, preferably 10000-50000 g / mol; Preferably, the molar ratio of the polyethylene glycol I to the L-lactide is 1:200-2000; Preferably, the molar ratio of the polyethylene glycol II to the D-lactide is 1:200-2000.

9. The method according to any one of claims 6 to 8, wherein: In step S3, the stirring conditions include: stirring time of 1-10 min, preferably 3-6 min, stirring temperature of 150-250° C., preferably 170-210° C.; Preferably, in step S4, based on the weight of the composite material, the mass of the inorganic mineral is 5wt%-70wt%, preferably 10wt%-50wt%; Preferably, the inorganic mineral is selected from at least one of calcium phosphate, hydroxyapatite, bioglass and calcium carbonate.

10. The method according to any one of claims 6 to 9, wherein: The processing and forming method is electrostatic spinning and / or 3D printing.

11. A composite material prepared by the method according to any one of claims 6 to 10.

12. Use of the composite material according to any one of claims 1 to 5 or 11 in bone tissue repair.